Application of the Quantum Learning Model to PGMI Students in Mathematics Learning - Manna Wassalwa (Yayasan Zia Salsabila, 2023)
The application of learning models that are less effective and innovative can lead to low student learning outcomes, so a learning model is needed that is able to motivate students to improve learning outcomes, especially in mathematics content. This study aims to determine the increase in student learning outcomes who get the Quantum Teaching learning model at the PGMI major in mathematics learning. Quantum Teaching provides the view that students in the learning process are important not just sitting and listening, but students need to be active to find their own knowledge. The method used in this study is a qualitative method with a descriptive approach. Based on research it is known that this quantum teaching learning model can increase motivation and understanding of learning in PGMI students in mathematics lessons.